IMPLEMENTATION OF THE ISLAMIC CULTURAL HISTORY (SKI) CURRICULUM IN 21ST CENTURY LEARNING 21 - Pujiati Pujiati; Andi Murniati (Jurnal Intelek Insan Cendikia, 2025)
Merdeka Curriculum is the latest 21st-century curriculum that provides diverse intracurricular learning, so students have adequate time to understand concepts and strengthen skills. Teachers can choose teaching methods tailored to students' needs and interests. In madrasas, one of the essential subjects is Islamic Cultural History (ICH), which discusses the development of Islam from the time before the entry of Islam to the present. SKI learning aims to provide students with an understanding of history so that they can take lessons from past events.Implementing the Merdeka Curriculum in Madrasas is based on applicable regulations, including guidelines from KEMENDIKBUD and KEMENAG, such as KMA 347 of 2022. One of the practical teaching methods in SKI learning is the role-playing method. This method was chosen based on its suitability to the teaching materials and students' abilities, thus creating flexible and engaging learning.